GURU SEBAGAI FASILITATOR DALAM MENGATASI KESULITAN BELAJAR PESERTA DIDIK PADA PEMBELAJARAN DARING [TEACHERS AS FACILITATORS IN OVERCOMING STUDENTS' LEARNING DIFFICULTIES DURING ONLINE LEARNING] - Putri S, Margaretha Ivana; Dirgantoro, Kurnia Putri Sepdikasari (JOHME: Journal of Holistic Mathematics Education, 2021)
During the Covid-19 pandemic, online learning became a new way of teaching and learning which utilized electronic devices, especially internet networks. However, in practice, online learning often encounters obstacles. With online learning, teachers need to know the causes and indicators of these difficulties. Efforts can then be made to alleviate them, namely that teachers become facilitators of online learning activities. In their role as facilitators, teachers can provide their students with supportive learning resources and media, encouragement and motivatation, and time outside of school hours to help students understand well. In this case, the author used a literature review and case study methods as the basis for preparing research instruments with the purpose of this paper being to explain the role of the teacher as a facilitator in overcoming learning difficulties of students during online learning. The author is aware of the limitations that humans have so the learning difficulties that students experience can be seen as an opportunity for teachers to serve those students. Teachers are also required to be more responsible for themselves and their students as a form of gratitude to God. The author suggests that the teacher as a facilitator can continue to learn to better understand the various strategies in overcoming learning difficulties and have a sense of responsibility towards students.BAHASA INDONESIA ABSTRACT: Dalam masa pandemi seperti ini, pembelajaran daring menjadi cara baru dalam proses belajar mengajar dengan memanfaatkan perangkat elektronik, khususnya jaringan internet. Namun dalam pelaksanaannya, pembelajaran daring sering mengalami kendala. Dalam pembelajaran daring yang dihadapi, guru perlu mengetahui faktor penyebab dan indikator kesulitan belajar daring. Kemudian, upaya dapat dilakukan yaitu guru diharapkan mampu menjadi fasilitator dalam kegiatan pembelajaran daring. Dengan perannya sebagai fasilitator, guru memberikan pelayanan berupa menyediakan sumber dan media pembelajaran yang mendukung, serta memberi semangat dan motivasi, serta meluangkan waktu di luar jam sekolah agar dapat membantu peserta didik memahami pembelajaran dengan baik. Dalam hal ini, penulis menggunakan metode kajian pustaka dan studi kasus sebagai dasar dalam penyusunan instrumen penelitian, dan tujuan penulisan paper adalah untuk menjelaskan guru sebagai fasilitator dalam mengatasi kesulitan belajar peserta didik selama pembelajaran daring. Penulis menyadari akan keterbatasan yang manusia miliki, sehingga melalui kesulitan belajar yang peserta didik alami dapat dilihat sebagai kesempatan untuk dapat melayani peserta didik. Guru juga dituntut lebih bertanggung jawab terhadap diri sendiri maupun peserta didik, sebagai wujud ucapan syukur kepada Tuhan. Saran penulis adalah agar guru sebagai fasilitator dapat belajar terus untuk lebih memahami berbagai macam strategi dalam mengatasi kesulitan belajar dan memiliki rasa tanggung jawab terhadap peserta didik.